Mapping The Student Teacher Candidates' Need Of Self-Regulated Learning Measuring Tools: A Rasch Model Analysis - Krismanto, Wawan; Muslimin, Muslimin; Sultan, Muh. Asrul (Seminar Nasional LP2M UNM, 2023)
Abstract. Much research has been carried out on the development of self-regulated learning scales aimed at measuring various subjects. However, existing research has not included an in-depth review of the needs map and instrument characteristics according to the subject to be measured. Therefore, this preliminary study on the development of a self-regulated learning scale is important and urgent to carry out as a basis for developing a scale. This research aims to map the needs of student teacher candidates on a scale to measure their self-regulated learning skills in learning and achieving competency as prospective teachers. In addition, it aims to identify the characteristics and format for the scale. Based on the objectives, survey research is a research strategy that is deemed appropriate. The sample for this research was 358 student teacher candidates. Data were analyzed using Rasch measurement model. The results show that a scale for measuring self-regulated learning skills and strategies is needed by student teacher candidates. This conclusion needs to be followed up by developing a scale of skills and self-regulated learning strategies specifically aimed at student teacher candidates. The development of this scale needs to pay attention to the characteristics of a good, appropriate and relevant scale.  Keywords: teacher candidates, self regulated, rasch model, scale needs